Liquid crystalline macrocyclic azacalix[4]pyridine and its complexes with the zinc ion: conformational change from the saddle to flattened shape. Issue 24 (25th February 2015) - Fa, Shi-Xin; Chen, Xiao-Fang; Yang, Shuang; Wang, De-Xian; Zhao, Liang; Chen, Er-Qiang; Wang, Mei-Xiang
Abstract : Regulation of phase behaviors by macrocyclic conformational variation. Abstract : Substituted with four 3, 4, 5-tris(alkoxy)benzyl mini-dendrons, azacalix[4]pyridine (1) with the saddle-shaped core is the first liquid crystal (LC) of heteracalixaromatics. Conformational regulation of azacalix[4]pyridine by complexing with the zinc ion leads to a significant change in LC properties.